Challenges That Health Care Systems Faced During and After the COVID-19 Pandemic - Dimitris Zavras (Healthcare, 2026)
The coronavirus disease 2019 (COVID-19) pandemic represented a global public health and economic crisis, which evolved into a humanitarian crisis, resulting in devastating fatalities and widespread suffering [...]